Students’ Perception of Using Reciprocal Teaching on Reading Comprehension of 9th Grade Students at SMP N 1 Pematangsiantar - Purba, Christian Neni; Manihuruk, Leonita Maria Efipanias; Sagala, Sepriyana; Damanik, Bernieke Anggita Ristia; Marpaung, Tiarma Intan (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyse students’ perceptions of the use of Reciprocal Teaching strategy in inferential level reading comprehension based on narrative text in 9th grade students at SMP N 1 Pematangsiantar. This research uses a descriptive quantitative approach using a closed questionnaire with a 4-point Likert scale. The sample is 32 students of grade IX.9 selected through a purposive sampling. Data were analysed using SPSS version 21. The results showed that overall, students’ perceptions of the application of Reciprocal Teaching were in the agree category with an average percentage of 83%. Specifically, the cognitive aspect obtained 84%, the affective aspect 85%, and the behavioural aspect 80%. These findings indicate that Reciprocal Teaching not only helps students understand texts both literally and inferentially but also increases motivation, interest, and active participation in reading activities. Therefore, this strategy can be recommended as an effective alternative in teaching reading comprehension of narrative text at the junior high school level.